Touching the void – First and third person perspectives in two cases of autobiographical amnesia linked to temporal lobe epilepsy. (February 2018) - Zeman, Adam; Byruck, Marcus; Tallis, Peter; Vossel, Keith; Tranel, Daniel
Abstract: Temporal lobe epilepsy (TLE) can be associated with a marked impairment of autobiographical memory. This is occasionally its presenting feature. We describe two individuals with severe epilepsy-associated autobiographical memory loss. Both MB and PT were reassured initially that their memory was intact on the basis of standard neuropsychological tests. Both have written detailed accounts of their symptoms. The key neuropsychological features of their cases are the relative normality of performance on standard memory tests, with preservation of semantic memory for impersonal information, in contrast to a profound amnesia for salient autobiographical episodes and an impoverishment of imaginative scene construction. First person accounts from these individuals illustrate the importance of autobiographical memory in sustaining a coherent sense of self, informing interpersonal relationships and supporting future thinking and problem-solving. These cases contribute to the growing evidence for a distinctive pattern of autobiographical memory loss associated with TLE, and indicate that it can take a severe form affecting both personal semantics and episodic recollection. Defining the phase of memory processing most relevant to this form of amnesia, and the roles of physiological and structural pathology, requires further research. The paper's title refers to the introspective 'void' highlighted by both MB and PT in their reports – in PT's words: 'My primary symptom is the void that is my past'. Highlights: Temporal lobe epilepsy can cause profound autobiographical amnesia (AbA). Performance on standard memory tests may be normal. The AbA impacts sense of self, interpersonal relationships and future planning. Epilepsy-related AbA can be mistaken for dissociative or 'psychogenic' amnesia.